The Unapologetic Mathematician

Mathematics for the interested outsider

The Codifferential

From our calculation of the square of the Hodge star we can tell that the star operation is invertible. Indeed, since *^2=(-1)^{k(n-k)}\lvert g_{ij}\rvert — applying the star twice to a k-form in an n-manifold with metric g is the same as multiplying it by (-1)^{k(n-k)} and the determinant of the matrix of g — we conclude that *^{-1}=(-1)^{k(n-k)}\lvert g^{ij}\rvert*.

With this inverse in hand, we will define the “codifferential”

\displaystyle\delta=(-1)^k*^{-1}d*

The first star sends a k-form to an n-k-form; the exterior derivative sends it to an n-k+1-form; and the inverse star sends it to a k-1-form. Thus the codifferential goes in the opposite direction from the differential — the exterior derivative.

Unfortunately, it’s not quite as algebraically nice. In particular, it’s not a derivation of the algebra. Indeed, we can consider fdx and gdy in \mathbb{R}^3 and calculate

\displaystyle\begin{aligned}\delta(fdx)&=-*d*(fdx)=-*d(fdy\wedge dz)=-*\frac{\partial f}{\partial x}dx\wedge dy\wedge dz=-\frac{\partial f}{\partial x}\\\delta(gdy)&=-*d*(gdy)=-*d(gdz\wedge dx)=-*\frac{\partial g}{\partial y}dy\wedge dz\wedge dx=-\frac{\partial g}{\partial y}\end{aligned}

while

\displaystyle\begin{aligned}\delta(fgdx\wedge dy)&=-*d*(fgdx\wedge dy)\\&=-*d(fgdz)\\&=-*\left(\left(\frac{\partial f}{\partial x}g+f\frac{\partial g}{\partial x}\right)dx\wedge dz+\left(\frac{\partial f}{\partial y}g+f\frac{\partial g}{\partial y}\right)dy\wedge dz\right)\\&=\left(\frac{\partial f}{\partial x}g+f\frac{\partial g}{\partial x}\right)dy-\left(\frac{\partial f}{\partial y}g+f\frac{\partial g}{\partial y}\right)dx\end{aligned}

but there is no version of the Leibniz rule that can account for the second and third terms in this latter expansion. Oh well.

On the other hand, the codifferential \delta is (sort of) the adjoint to the differential. Adjointness would mean that if \eta is a k-form and \zeta is a k+1-form, then

\displaystyle\langle d\eta,\zeta\rangle=\langle\eta,\delta\zeta\rangle

where these inner products are those induced on differential forms from the metric. This doesn’t quite hold, but we can show that it does hold “up to homology”. We can calculate their difference times the canonical volume form

\displaystyle\begin{aligned}\left(\langle d\eta,\zeta\rangle-\langle\eta,\delta\zeta\rangle\right)\omega&=d\eta\wedge*\zeta-\eta\wedge*\delta\zeta\\&=d\eta\wedge*\zeta-(-1)^k\eta\wedge**^{-1}d*\zeta\\&=d\eta\wedge*\zeta-(-1)^k\eta\wedge d*\zeta\\&=d\left(\eta\wedge*\zeta\right)\end{aligned}

which is an exact n-form. It’s not quite as nice as equality, but if we pass to De Rham cohomology it’s just as good.

About these ads

October 21, 2011 - Posted by | Differential Geometry, Geometry

No comments yet.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

Follow

Get every new post delivered to your Inbox.

Join 389 other followers

%d bloggers like this: